Correlation between Infection of Soil Transmitted Helminths (STH) and Peripheral Blood Eosinophil Levels amongElementary Student at Barengan Village, Teras Subdistrict, Boyolali. - Nadhiasari, Aulia; Sakiman, Bambang Sukilarso; Dirgahayu, Paramasari (Nexus Biomedika, 2015)
Background: The Parasitic infection, caused by intestinal helminths, accounts for significans burden of human disease in developing countries including Indonesia. In chronic infection, eosinophilia occurs as protection against helminth parasites.Â Increasing eosinophils is often associated with diseases, such as allergy, nephrotic syndromes, leoffler diseases, and also helminthiasis. However, there are little data to prove this unequivocally. This study aimed to determine the correlation between soil transmitted helminths infections and the levels of peripheral blood eosinophil among elementary students at Barengan Village, Teras Subdistrict, Boyolali Methods: This study was conducted by an observational analytic research in a cross sectional approach at Elementary School students in Barengan Village, Teras Subdistrict, Boyolali on periode of October-November 2014. We conducted on 74 samples according to the inclusion and exclusion criteria. The data were collected from stool, peripheral blood and questionnaires and then were statistically analyzed with Chi Square test to determine their correlation. Results: Our study showed that the prevalence of helminthiasis among student was 47.3% and Chi Square Analyzes between STH infection and eosinophilia had the value ofÂ p=0.041 with Odds Ratio= 2.695. Conclusions:Barengan Village, Teras Subdistrict, Boyolali is still an endemic area for helminthiasis (47.3%). This study shows correlation between soil transmitted helminthes infections and increasing the levels of peripheral blood eosinophil among elementary students at Barengan Village, Teras Subdistrict, Boyolali. Keywords: Soil transmitted helminths, eosinophil, elementarystudents of SD Barengan